Creating a Multilingual and Multicultural Learning Environment: A Case Study of a Japanese Culture Course at a College Level in Japan - Koshiyama, Yasuko; Aliponga, Jonathan; Itou, Hajime (Lingua Posnaniensis, 2019)
More and more international students come to Japan to study. Data shows that they tend to face learning related difficulties. Our study’s goal was to determine whether or not the English and Japanese hybrid class has created a multilingual and multicultural learning environment. Pre-instructional and post-instructional surveys were taken by the students taking the class, and the data was compared between high achievers and non-high achievers, and between Japanese students and international students. The results show that high achievers and non-high achievers, and Japanese students and international students all had positive perceptions of the class contents and instruction in Japanese and English. These findings tell us that the English and Japanese hybrid class provided meaningful and purposeful opportunities for creating a multilingual and multicultural learning environment for all groups and students. This was achieved by contextualizing relevant and appropriate topics and themes, such as social and cultural characteristics and issues of Japan and utilizing the target languages of English and Japanese for hybrid instruction.